RETRACTED: Recovery through breathing: The role of respiratory practices in the rehabilitation of students after COVID19 - Ryzhkin Nikolay; Tumasyan Tatiana; Brovashova Olga; Stepicheva Natalia (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001